Pengaruh Struktur Modal terhadap Kinerja Keuangan Dengan Tata Kelola Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia - Agnita Putri Mawaddah; Rosyeni Rasyid (Dinasti Review, 2025)
This study was conducted to determine the effect of capital structure on financial performance with corporate governance as a moderating variable in property and real estate companies listed on the Indonesia Stock Exchange. The study population consisted of 93 property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. Meanwhile, the sample in this study was determined using the purposive sampling method, so that 16 sample companies were obtained with a total of 80 observations (16 companies x 5 years). The data used are secondary data obtained from the official website of the Indonesia Stock Exchange and the company's official website. Data analysis was carried out using panel data regression and Moderate Regression Analysis (MRA) with the help of Eviews 12 software. The results of the study show that (1) Capital structure has a partial effect on financial performance, where Long Term Debt to Total Asset (LDTA) has a significant negative effect on Return On Equity (ROE) and Short Term Debt to Total Asset (SDTA) shows a positive insignificant effect on Return On Equity (ROE). (2) Corporate governance as measured by managerial ownership (MOWN) and institutional ownership (IOWN) has not been able to moderate the influence of capital structure on financial performance.